Soil macrofauna of the middle taiga forests at the Lyalsky test area in the European part of Russia (Komi Republic) ... - Konakova, Tatyana; Ditts, Alla (Institute of Biology of Komi Scientific Centre of the Ural Branch of the Russian Academy of Sciences, 2024)
Data on the number of individuals of large soil invertebrates in soil samples collected in spruce, pine and deciduous forests at the Lyalsky test area in the European part of Russia (Komi Republic) are presented. A total of 356 occurrences are included in the resource. ...